Involvement of Mast Cells in the Pathophysiology of Pain - Mai, Lijia; Liu, Qing; Huang, Fang; He, Hongwen; Fan, Wenguo (Frontiers in Cellular Neuroscience, 2021)
Mast cells (MCs) are immune cells and widely distributed throughout the body. MCs are not only classically viewed as effector cells of some allergic diseases but also participate in host defense, innate and acquired immunity, homeostatic responses and immunoregulation. Mounting evidence indicates that activation of MCs releasing numerous vasoactive and inflammatory mediators has effects on the nervous system and has been involved in different pain conditions. Here, we review the latest advances made about the implication of MCs in pain. Possible cellular and molecular mechanisms regarding the crosstalk between MC and nervous system in the initiation and maintenance of pain are also discussed.